Molecular studies of coronavirus replication and pathogenesis - Li, Qisheng (2008)
Host factors participate in most steps of virus life cycle. Concomitantly, host gene expression and defenses are modulated by viruses to optimize viral replicatio. Identifying virus-host interactions can help define mechanisms of viral pathogenesis within the host cell as well as the roles of individual viral protein during infection.